BEBAN KERJA DAN SIKAP PERAWAT TERHADAP PELAKSANAAN KOMUNIKASI TERAPEUTIK - Rakinaung, Natalia; Laka, Angela; Talumepa, Treyse (Lasalle Health Journal, 2024)
Background: Nurses are human resources that have a major impact on hospital services. One of the implementations of good nursing care is the application of therapeutic communication, so that they can adapt to the problems they face and can take appropriate action for their health. Objective: This study aims to analyze the relationship between workload and attitudes towards the implementation of therapeutic communication for nurses in hospitals. Method: This study uses a descriptive quantitative design with a cross-sectional approach. The population consisted of 31 nurses in the inpatient ward, and the sampling technique was total sampling with 31 respondents, with instruments using 3 questionnaires, namely the workload questionnaire, attitude questionnaire and therapeutic communication questionnaire. Results: Shows that workload is related to the implementation of therapeutic communication for nurses and attitudes are related to the implementation of therapeutic communication for nurses. Conclusion: There is a relationship between workload and attitudes of nurses with the implementation of therapeutic communication for nurses in hospitals.